Engaging Learners to Advance Medical Education. (April 2017) - Burk-Rafel, Jesse; Jones, R. Logan; Farlow, Janice L.
Abstract : Learners are a pillar of academic medicine, yet their voice is seldom heard in national and international scholarly conversations on medical education. However, learners are eager to contribute: in response to a recent open call from Academic Medicine, medical students and residents representing 98 institutions across 11 countries submitted 224 Letters to the Editor on wide-ranging topics. In this Invited Commentary, the authors—three medical students serving in national leadership roles—contextualize several themes discussed in these learner-authored letters. The authors first explore the unique voice learners contribute to educational innovation, highlighting the value learners add to curricular and systemic educational reform efforts. They then turn to the broader implications of the many submitted letters addressing the culture and humanism of medicine, proposing that learners can be powerful catalysts and partners in cultural change. Despite these benefits, the authors note that learners are largely untapped change agents who are particularly underrepresented in medical education scholarship, finding that students were just 2.8% (39/1, 396) of authors and 3.5% (12/340) of first authors among all print publications in Academic Medicine in 2016. The authors conclude by offering tangible steps for the academic medical community to engage learners in leadership, advocacy, and scholarship.